Efficacy and safety of hydromorphone for postoperative patient-controlled intravenous analgesia for patients undergoing orthopedic surgery: a randomized, double-blinded controlled trial - Qi Wang; Yuanyuan Zhao; Bin Ling; Xiangxiang Chen; Yayun Xie; Haibo Zhao; Jiangang Zhang; Wei Wang; Jie Lv (Frontiers in Medicine)
BackgroundThe study aimed to evaluate the efficacy and safety of hydromorphone in postoperative patient-controlled intravenous analgesia (PCIA) for orthopedic surgery patients, offering a reference for postoperative pain management in this patient population.MethodsThis was a prospective, randomized, double-blinded, controlled trial involving 80 patients aged 23 to 64 years undergoing elective orthopedic surgery. All participants were randomly assigned to the test group (Group H) and the control group (Group C) by the random number table method. In Group H, hydromorphone (0.2 mg/kg) and palonosetron (4 μg/kg) diluted to 150 mL with saline were used for PCIA, while in Group C, sufentanil (2 μg/kg) and palonosetron (4 μg/kg) were diluted to the same volume. Postoperative pain was assessed using the resting Visual Analog Scale (VAS) at 2, 6, 12, 24, and 48 h postoperatively. The total and effective PCIA button presses within 48 h, along with the number of remedial analgesia cases, were recorded. Ramsay, Awakening time, extubation time, hospital stay duration, and adverse events within 48 h postoperatively were also recorded.ResultsCompared to Group C, Group H had significantly lower VAS scores at 2 and 6 h, as well as Ramsay, SDS, and PSQI scores at 24 and 48 h postoperatively (all p < 0.01). Furthermore, the incidence of dizziness and drowsiness within 48 h postoperatively was significantly reduced in Group H (p = 0.007 and p = 0.003, respectively).ConclusionHydromorphone-based PCIA enhances early postoperative pain relief in orthopedic surgery patients, alleviates postoperative depression and sleep disturbances, and reduces the incidence of dizziness and drowsiness.Clinical trial registrationThis study was registered in the Chinese Clinical Trial. Registry (www.chictr.org.cn) on 01/04/2024 (ChiCTR2400082567).